2021
DOI: 10.1111/ejh.13597
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in multiple myeloma and implications on survival: A population‐based study

Abstract: High proportion of patients with multiple myeloma suffer from comorbidities which may alter clinical management. Therefore, our aims were to evaluate the prevalence of comorbidities and their impact on survival. We included patients diagnosed with multiple myeloma 1990‐2013 in Sweden and all diagnoses from each patient from 1985. A total of 13 656 patients with multiple myeloma were included in the study, thereof 7404 (54%) had comorbidity at diagnosis. The risk of death was increased for those with one comorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Unlike these studies, the racial survival differences in MM were not statistically significant when matching on demographic variables. In sharp contrast, after adequately matching on presentation, NHBs had significantly longer survival than NHWs, suggesting the associations between increased number of comorbidities in NHBs and decreased survival [ 30 ]. The racial survival disparities were further enlarged after sequential matching on treatment which confirmed the effects of the observed treatment disparity on the survival disparity even among patients matched for presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike these studies, the racial survival differences in MM were not statistically significant when matching on demographic variables. In sharp contrast, after adequately matching on presentation, NHBs had significantly longer survival than NHWs, suggesting the associations between increased number of comorbidities in NHBs and decreased survival [ 30 ]. The racial survival disparities were further enlarged after sequential matching on treatment which confirmed the effects of the observed treatment disparity on the survival disparity even among patients matched for presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that patients with MM who had arrhythmias had a higher Charlson Comorbidity Index. A study in Sweden found higher comorbidities in patients with MM with an associated increased risk of death in those with arrhythmias 34. On further analyses of comorbidities associated with inpatient mortality among patients with MM with arrhythmias, acute MI, CVD, renal disease, and metastatic cancer were found to predict higher inpatient mortality.…”
Section: Discussionmentioning
confidence: 95%
“…While mortality in MM declined in all other age groups, it modestly increased in those aged 80 + years. A recent Swedish study showed that over half of MM patients have comorbidities and these correlated with age and survival disadvantage 24 . Thus competing fatal causes are likely to be most prevalent among the old.…”
Section: Discussionmentioning
confidence: 99%